Ketahanan Industri Logistik dalam Keadaan Darurat Nasional - Saduddin Saduddin; Jan Prabowo Harmanto; Mohamad Rachmadian Narotama; Yuveline Aurora; Herawati Basirpuly; Sarah Auliya Furjatullah (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2022)
This research is conducted to comprehensively understand the impact of Covid-19 pandemic on the Indonesian logistics service industry, which has created the economic downturn worldwide. The response and adaptation of the logistics service providers and the intervention and strategies needed to preserve the Indonesian logistics industry were observed. The adaptation plan was carried out in various sectors such as the business sector, information and communication technology, information and communication technology infrastructure, and organizational infrastructure. Using questionnaire to survey and doing an in-depth interview to 30 logistics service providers from associations and logistics business entities, it is found that most of the logistics service industry experience a decline in activities as the result of the movement restrictions. There is still a challenge; unpredictable span time of pandemic, despite the spontaneous adaptations made to maintain operations. Therefore, the role of policy makers in the industry is needed to propose various adaptation and intervention strategies to maintain the Indonesian logistics services industry.